Struktur Cerkak Ing Kene Ana Cahya - Ratu, Aurora Kusuma; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
Javanese short stories are one of the genres in modern Javanese literature. Short stories (short stories) in modern Javanese literature are called cekak stories (cerkak). The focus of the study of Javanese short stories is short stories contained in Javanese magazines, such as Jaya Baya magazine and Panyebar Semangat magazine. One of the stories that has pana magazine panjebar semangat is a cerkak entitled